2013
DOI: 10.1177/1464700113483249
|View full text |Cite
|
Sign up to set email alerts
|

A beleza abre portas: Beauty and the racialised body among black middle-class women in Salvador, Brazil

Abstract: Beauty is constantly lived and incorporated as a meaningful social category in Brazil and intersects with racialised and gendered ways of belonging to the Brazilian nation. In this article, I deploy ethnographic material to show how middle-class women self-identifying as black embody and experience beauty and how, through practices and discourses centred on physical appearance, they both reinforce and challenge broader social and racial inequalities in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 23 publications
0
4
0
4
Order By: Relevance
“…Gathering a wider variety of national case studies will develop relational approaches in Black middle‐class studies. Research in Brazil has shown how Black women in middle‐class families engage in Eurocentric beauty practices to achieve more respectable middle‐class feminine identities (Gordon, ), research in Mexico has shed light upon how poor rural Afro‐Mexicans view middle‐class Afro‐Mexicans as part of the state administration, which dominates them (Lewis, ), and research in Nigeria shows how richer “native” populations prefer schools with White teachers and Eurocentric curricula (Ayling, ). These findings bear consistency with themes explored in this paper.…”
Section: Conclusion: Setting the Scene For Relational Studiesmentioning
confidence: 99%
“…Gathering a wider variety of national case studies will develop relational approaches in Black middle‐class studies. Research in Brazil has shown how Black women in middle‐class families engage in Eurocentric beauty practices to achieve more respectable middle‐class feminine identities (Gordon, ), research in Mexico has shed light upon how poor rural Afro‐Mexicans view middle‐class Afro‐Mexicans as part of the state administration, which dominates them (Lewis, ), and research in Nigeria shows how richer “native” populations prefer schools with White teachers and Eurocentric curricula (Ayling, ). These findings bear consistency with themes explored in this paper.…”
Section: Conclusion: Setting the Scene For Relational Studiesmentioning
confidence: 99%
“…Assim, um lugar frequentado por "gente bonita" faz menção a um espaço social de circulação de pessoas das camadas médias e altas e de tez clara, ao mesmo tempo em que a feiura é atribuída genericamente a pessoas "pretas e pobres". "Boa aparência", termo comumente empregado para descrever requisitos para vagas de trabalho 12 , designa, de forma implícita, a preferência por candidatos/as brancos/as ou de tez clara e de aparência e comportamento identificados com códigos das classes médias (Caldwell 2007;Carneiro 2003b;Gonzalez 1984;Gordon 2013;Jarrín 2017).…”
Section: Estéticaunclassified
“…Há uma atenção acentuada à tonalidade da pele e textura dos cabelos, com preferência pela tez branca e pelos tons de pele morena mais claros, pelos cabelos lisos ou, no máximo, ondulados. Nariz "largo", pele escura, cabelos cacheados a crespos e lábios "grossos" são considerados feios, e, ocasionalmente, associados à animalidade (Edmonds 2007a(Edmonds , 2007bGonzalez 1984;Gordon 2013;Jarrín 2017;Twine 1998). Certos sinais referidos à negritude são, por vezes, enaltecidos, como se vê na preferência nacional pela "bunda" grande.…”
Section: Estéticaunclassified
See 1 more Smart Citation
“…1 They underlie racist stereotypes and associated acts of stigmatisation (Lamont et al 2016). They structure ideas about beauty, especially for women who are particularly marked by and sensitive to the negative values attached to the skin tones, hair textures and facial features associated with black and indigenous people (Edmonds 2007;Gordon 2013;Nichols 2013;Rahier 1999). They enter into the intimate domains of the family, where they can guide decisions about romantic relationships and reproduction, and can differentiate in a finegrained way between darker and lighter siblings (Hordge-Freeman 2015; Moreno Figueroa 2012;Roberts 2012).…”
Section: Racism and Mestizajementioning
confidence: 99%